The Freedom Budget at 45: Functional finance and full employment - Mathew Forstater (Levy Economics Institute of Bard College, 2011)
Forty-five years ago, the A. Philip Randolph Institute issued The Freedom Budget, in which a program for economic transformation was proposed that included a job guarantee for everyone ready and willing to work, a guaranteed income for those unable to work or those who should not be working, and a living wage to lift the working poor out of poverty. Such policies were supported by a host of scholars, civic leaders, and institutions, including the Rev. Dr. Martin Luther King Jr.; indeed, they provided the cornerstones for King's Poor Peoples' Campaign and economic bill of rights. This paper proposes a New Freedom Budget for full employment based on the principles of functional finance. To counter a major obstacle to such a policy program, the paper includes a primer on three paradigms for understanding government budget deficits and the national debt: the deficit hawk, deficit dove, and functional finance perspectives. Finally, some of the benefits of the job guarantee are outlined, including the ways in which the program may serve as a vehicle for a variety of social policies.
Keywords: B500; E240; E610; H600; P160; 330; unemployment; full employment; budget deficits; national debt; public policy; Vollbeschäftigung; Recht auf Arbeit; Beschäftigungspolitik; Sozialpolitik; Öffentlicher Haushalt; Öffentliche Schulden; USA